Vanishing Land and Water - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Vanishing Land and Water Soil and water conservation in dry lands, by Jean-Louis Chleq and Hugues Dupriez in the series Terres et Vie (Land and Life) by Macmillans